Stres dan Kualitas Tidur dengan Kadar Gula Darah Puasa pada Lansia DM Tipe II - Frestyan Setya Nugraha; Brune Indah Yulitasari; Tengku Isni Yuli Lestari Putri (STIKes Surya Global Yogyakarta, 2022)
Background: One of the important factors that occur in the elderly is decrease of health condition such as Diabetes Mellitus type II. This condition is supported by psychological conditions such as stress receptors of the elderly. High stress will affect the quality of sleep. Where stress and sleep quality affect blood sugar in the elderly to become unstable which can harm Diabetes Mellitus patients.Objective: This study aims to identify the correlation between stress levels and sleep quality with fasting blood sugar levels in the elderly suffering from Diabetes type II at the Kasihan II Public Health Center, Bantul, YogyakartaMethods: This research was descriptive-analytic research with a cross-sectional approach. The sample in this study was taken using a purposive sampling technique with 51 elderly respondents with Diabetes Mellitus type II. The research instrument used the Diabetes Distress Scale (DDS), the Pittsburgh Sleep Quality Index (PSQI), and the Glucometer.Results: The statistical test was used the Spearman rank test. The results in this study there was relationship between stress levels and sleep quality in the elderly with type II diabetes, it was evidenced by the P-value 0.000 (stress level with GDP) and P-value 0.003 (sleep quality with GDP).Conclusion: It can be concluded that there is a significant relationship between stress levels, sleep quality with fasting blood sugar levels in the elderly suffering from type II diabetes at the Kasihan II Public Health Center, Bantul, Yogyakarta.Keywords: DM Type 2, Elderly, Stress